Works from the Crex Collection, Zürich. - Raussmüller, Urs; Fuchs, R.H (Zürich : Sammlung Crex, 1978)
Baselitz, Georg ; Becher, Bernd & Hilla ; Broodthaers, Marcel ; Brouwn, Stanley ; Byars, James Lee ; Darboven, Hanne ; Dibbets, Jan ; Gilbert & George ; Judd, Donald ; Kawara, On ; Kounellis, Jannis ; LeWitt, Sol ; Long, Richard ; Lüpertz, Markus ; Mangold, Robert ; Nauman, Bruce ; Palermo, Blinky ; Penck, A.R. ; Polke, Sigmar ; Richter, Gerhard ; Ryman, Robert ; Weiner, Lawrence
Works from the Crex Collection, Zürich / Werke aus der Sammlung Crex, Zürich, InK, Zürich ; Louisiana Museum, Humlebaek ; Städt. Galerie im Lenbachhaus, München ; Stedelijk Van Abbemuseum, Eindhoven
Duits & Engels
kunstcatalogus